Dziecko - Nauczyciel - Arteterapia = Child - Teacher - Art therapy - Maciejewska, Tatiana; Samulczyk, Teresa (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The aim of the article is to show arttherapy activity taken with University of Zielona Góra students and early childhood education teacher. The paper shows possibility of using different art disciplines in the educational process. Discusses the ways of creating "learning situations" like creative attitude, allowing children to contact with the art and to test themselves in creative activities. Article emphasizes the essence of fun in the theater, games, drama and dance improvisation.
Keywords: arteterapia; teatr; taniec; gry dramatyczne; art therapy; theatre; dance theatre; drama